Ancient India's Classical Alphabetical System Innovates, Evaluates, and Expands the History of Brahmi Scripts: Proofs, Prospects and Authenticity - Islam, Md Amirul; Khatun, Baly (Universitas Brawijaya, 2024)
This study was an attempt to prove the Brahmi origin, evolution, expansion of history, significance, relationship with other writing systems, and alphabetical cultural heritage. This paper was aimed at clarifying the queries about Brahmi scripts using all current data. This study used qualitative, quantitative, statistical and past manuscripts and thinking methods. This study shows differences between northern and southern Brahmi in such things as language, country, people, vowels, and consonants: 25, 11, 1.06E+09, 233, and 677; but in next, 24, 11, 5.15E+08, 262, and 554respectively. Finally, this paper proves that the Brahmi script is well expanded in the northern scripts.